1988
DOI: 10.7326/0003-4819-108-5-663
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Metabolic Effect of Omega-3 Fatty Acids in Non-Insulin-Dependent Diabetes Mellitus

Abstract: Increased interest in using omega-3 fatty acids led us to examine their metabolic effects in six men with type II (non-insulin-dependent) diabetes mellitus. After 1 month of a diet supplemented with these fatty acids, the patients' fasting glucose rose from 13.1 +/- 1.3 to 15.3 +/- 1.3 mmol/L (P = 0.03) and glucose area during a mixed meal profile rose by 22% (P = 0.04). Basal hepatic glucose output rose from 97 +/- 9 to 122 +/- 8 mg/m2 . min (P = 0.004) but glucose disposal rates measured by euglycemic glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
1
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(99 citation statements)
references
References 41 publications
5
91
1
2
Order By: Relevance
“…High dose EPA and DHA deteriorates glycemic control [20][21][22] , thus rationalizing the current study on high dose ALA.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…High dose EPA and DHA deteriorates glycemic control [20][21][22] , thus rationalizing the current study on high dose ALA.…”
Section: Introductionsupporting
confidence: 61%
“…However, several studies in the 1980s showed a deterioration of glycemic control in type 2 diabetes consuming high doses of fish oil containing eicosapentaenoic acid (EPA, 20:5 n-3) and docosahexaenoic acid (DHA, 22:6 n-3) or purified EPA or DHA [20][21][22] . However, lower doses of fish oil or purified EPA or DHA resulted in no change in glycemic control 21,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be ruled out that a longer period of dietary intervention would give different results. Also, the possible influence of the relative increase in n-3 FA, which may have a particularly negative influence on insulin secretion (12), has to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil also improved dyslipidaemia, hypertension and endothelial function in subjects with diabetes [22,23]. However, intake of n-3 FA has been associated with impaired glycaemic control, leading both to hyperglycaemia and insulin resistance [24,25]. In view of these inconsistent studies, proof that n-3 long chain polyunsaturated fatty acids (LC-PUFA) can prevent subjects with insulin resistance or impaired glucose tolerance from developing type 2 diabetes remains to be established.…”
Section: Introductionmentioning
confidence: 99%